The Reason South Korea Approved The Placement of A High Altitude Area Defense (THAAD) Terminal System in 2016 - Anouphone Inthaly; Agung Risdhianto; Aris Sarjito (Faculty of Social Science, Universitas Negeri Padang, 2022)
The United States counts South Korea as one of its most significant allies. Relations between the two countries began when the US and South Korea became military allies in the early 1950s, with the US promising to assist South Korea in defending itself against any North Korean assault. Since 2014, the US has attempted to include South Korea in the East Asia region's anti-missile defense system, but it has always been refused. There are several causes for this, including disagreements among South Koreans, relations with China, and complaints from neighboring countries such as China, North Korea, and Russia. South Korea, on the other hand, stated on July 8, 2016, that the United States would be placed in a special category. However, on July 8, 2016, South Korea stated that the Terminal High Altitude Area Defense (THAAD) anti-missile defense system from the United States would be stationed in the country. This oddity piqued the writer's interest, prompting him to investigate the reasons behind South Korea's approval of THAAD placement in 2016. This research is expected to have an impact on decision-makers in choosing a defense strategy that reduces the risk of security dilemmas as has happened in South Korea.